2018
DOI: 10.21037/gs.2018.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Late complications of radiation therapy for breast cancer: evolution in techniques and risk over time

Abstract: Radiation therapy in combination with surgery, chemotherapy, and endocrine therapy as indicated, has led to excellent local and distant control of early stage breast cancers. With the majority of these patients surviving long term, mitigating the probability and severity of late toxicities is vital. Radiation to the breast, with or without additional fields for nodal coverage, has the potential to negatively impact long term cosmetic outcome of the treated breast as well as cause rare, but severe, complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 57 publications
0
28
0
2
Order By: Relevance
“…40 Incidental radiation exposure of the heart, lungs, and contralateral breast may occasionally result in complications in these organs, especially in patients who receive radiotherapy after mastectomy. 39 , 41 …”
Section: Impact Of Cancer Treatment On Patients With Breast Cancermentioning
confidence: 99%
“…40 Incidental radiation exposure of the heart, lungs, and contralateral breast may occasionally result in complications in these organs, especially in patients who receive radiotherapy after mastectomy. 39 , 41 …”
Section: Impact Of Cancer Treatment On Patients With Breast Cancermentioning
confidence: 99%
“…By comparison, modern radiotherapy regimens allow for the completion of whole breast irradiation in only 3-4 weeks with low rates of toxicity. 11,[19][20][21] This study has several important limitations. It is a retrospective analysis using data from participating institutions, which mainly represent hospital-based practices accredited by the American College of Surgeons Commission on Cancer.…”
Section: Discussionmentioning
confidence: 96%
“…With regards to contralateral breast cancer, it has been demonstrated that the most important prognostic factor is age at first diagnosis, 18 again suggesting that this benefit of endocrine therapy is more important in the younger patient population. By comparison, modern radiotherapy regimens allow for the completion of whole breast irradiation in only 3‐4 weeks with low rates of toxicity 11,19‐21 …”
Section: Discussionmentioning
confidence: 99%
“…Techniques currently employed to help minimize exposure of normal breast and lymph tissue to radiation include intensity modulated radiation therapy, deep-inspiration breath hold, and hypofractionation, but risk of acute and late adverse events are still considerable. 18 There is a lack of evidence demonstrating that accelerated courses using high dose radiation improve long-term survival outcomes for breast cancer patients, including those with evidence of residual disease after lumpectomy. 19 Partial breast irradiation may be an option for some women, but this does not reduce treatment duration and has not been shown to improve patient outcomes compared to whole breast irradiation.…”
Section: Introductionmentioning
confidence: 99%